A phase 1 study of safety and immunogenicity following intradermal administration of a tetravalent dengue vaccine candidate. Issue 27 (22nd June 2018) - Jackson, Lisa A.; Rupp, Richard; Papadimitriou, Athanasia; Wallace, Derek; Raanan, Marsha; Moss, Kelley J.
Highlights: A low-dose formulation of Takeda's dengue vaccine candidate (LD-TDV) was injected intradermally. One or two doses of LD-TDV were well tolerated by dengue-naïve subjects. All regimens elicited neutralizing antibodies, similar in magnitude with one or two doses. Seroconversion was more rapid with a single dose by intradermal device rather than needle/syringe. Administration route had little or no effect on the immune responses to the different serotypes. Abstract: Background: As part of the ongoing search for an effective dengue vaccine, Takeda performed a phase 1b study to investigate the safety and immunogenicity of an early low-dose tetravalent dengue vaccine candidate formulation (LD-TDV), based on an attenuated serotype 2 backbone, when administered intradermally with an injector device (PharmaJet®), or needle-syringe. Methods: The study was performed in two centers in the US, in healthy 18–45 year old subjects with no history of dengue vaccination or disease. One or two vaccine doses were given on Day 0, and another dose or placebo on Day 90. Neutralizing antibodies were measured up to Day 270; safety was assessed as laboratory measurements and solicited and unsolicited adverse events on diary cards. Results: Changes in World Health Organization prequalification guidance for new vaccines concerning storage conditions favored the use of lyophilized preparations, and led to the early cessation of enrolment, but not before 67 subjects were enrolled in four treatment groups. Sixty-five subjects completed the planned schedule. There were no safety signals or serious adverse events. All vaccination regimens elicited neutralizing antibodies. Titers of neutralizing antibodies against serotypes 1 and 2 were higher than those against serotypes 3 and 4. There were no consistent increases in responses with two doses given either concomitantly or 90 days apart. Conclusions: Simultaneous injection of two LD-TDV doses was shown to have the potential to improve seroconversion rates to serotypes 1 and 2, and to increase serotype 2 antibody titers. A primary dose of LD-TDV administered by PharmaJet was shown to induce more rapid seroconversion to serotypes 1, 2, and 3 compared with administration by needle-syringe (ClinicalTrials.gov : NCT01765426).